Early speech therapy diagnosis of a child with apraxia and childhood aphasia - Olempska-Wysocka, Magdalena (Interdyscyplinarne aspekty diagnozy i terapii logopedycznej, 2020)
Diagnosis of specific speech development disorders is an interdisciplinary procedure, taking into account not only the child’s speech examination but also the results of psychological, audiological, neurological, psychiatric and other examinations. The article presents numerous studies and observations of children with apraxia and childhood aphasia, which allowed for the identification of indicators for early detection of specific speech disorders. Therefore, early logopedic diagnosis is important, which on the one hand is a planning process with the use of appropriate standards of conduct. On the other hand, it must be a process conducted by an interdisciplinary team of specialists in cooperation with the child’s parents.